PENGARUH METODE PEMBELAJARAN AUDITORY, INTELECTUALITY, REPETITION (AIR) TERHADAP HASIL BELAJAR EKONOMI - Zainal, Vetri Yanti (Lentera: Jurnal Ilmiah Kependidikan, 2018)
This research uses experimental method that is by using method of learning Auditory, Intellectuality, Repetition (AIR). From hypothesis testing using ttest statistic formula to know whether there is influence of application of learning method of learning of Auditory, Intelectuality, Repetition (AIR). After testing hypothesis on test of difference of two mean and calculation of data of economic learning result by using statistic formula, hence in can thit = 4,38 and ttab = 2.00 at 5% significant level so that proved that hit hit> ttab .. With so it can be concluded "There is influence of learning method of Auditory, Intellectuality, Repetition (AIR) to student's economic learning result of class X even semester SMA Negeri 2 Menggala year lesson 2016/2017". Judging from the mean score of the students, the experimental class x Ì…_ = 83.37 and the control class had an average value of x Ì…_ = 71.03. So the average students' economic learning outcomes using Auditory, Intellectuality, Repetition (AIR) learning methods are higher than students using conventional learning methods.